2002
DOI: 10.3758/bf03195773
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and retrospective memory in normal aging and dementia: An experimental study

Abstract: Two experiments investigatedthe effects of normal aging and dementia on laboratory-basedprospective memory (PM) tasks. Participants viewed a film for a later recognition memory task. In Experiment 1, they were also required either to say "animal" when an animal appeared in the film (event-based PM task) or to stop a clock every 3 min (time-based PM task). In both tasks, young participants were more successful than older participants, who were, in turn, more successful than patients with Alzheimer's disease (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
109
2
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 53 publications
16
109
2
7
Order By: Relevance
“…The mean proportion of cues that elicited a correct response at the appropriate moment in each Method of Encoding x Cue-Action Relatedness x Age Group condition was calculated, and is displayed in Figure 1. Prospective memory performance conditional on retrospective recall of PM task content Maylor et al (2002), among others, have suggested that participants may perform poorly in a PM task, not necessarily because of a PM failure but because of a retrospective memory failure i.e., failure to recall the content of the PM task. As Table 1 illustrates, most participants correctly recalled all 6 cue-action word pairs on completion of the ongoing task.…”
Section: Prospective Memory Performancementioning
confidence: 99%
“…The mean proportion of cues that elicited a correct response at the appropriate moment in each Method of Encoding x Cue-Action Relatedness x Age Group condition was calculated, and is displayed in Figure 1. Prospective memory performance conditional on retrospective recall of PM task content Maylor et al (2002), among others, have suggested that participants may perform poorly in a PM task, not necessarily because of a PM failure but because of a retrospective memory failure i.e., failure to recall the content of the PM task. As Table 1 illustrates, most participants correctly recalled all 6 cue-action word pairs on completion of the ongoing task.…”
Section: Prospective Memory Performancementioning
confidence: 99%
“…Some studies reported significant age effects (e.g. Maylor et al 2002;Smith and Bayen 2006;West and Craik 2001;Zimmerman and Meier 2006), while others failed to obtain age effects (e.g. Cherry and Plauche 2004;Marsh et al 2007;Reese and Cherry, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There is no recording of the intention on a to-do list; rather, the person is relying on the environmental cue to trigger recollection of the intention at a time when it is convenient to fulfill the task. The fragility of this type of memory is amply demonstrated by the numerous variables that have been shown to affect it-namely, how engrossed one is in other activities (e.g., Marsh, Hancock, & Hicks, 2002;, how distinctive or familiar the cue is from the background (McDaniel & Einstein, 1993), whether the current context matches the encoding context (McDaniel, Robinson-Riegler, & Einstein, 1998), and whether one is impaired by aging (e.g., Maylor, 1998) or by being a member of a neuropsychologically impaired population (Maylor, Smith, Della Sala, & Logie, 2002). From this perspective it is amazing that people successfully rely on this strategy in their everyday life, but they do (Marsh, Hicks, & Landau, 1998).…”
mentioning
confidence: 99%